Design, Fabrication and Technical Assessment of Isolated Multi Patient VAC systems for Diabetic Wound Ulcers - Prasad T., Arun; P., Manimegalai; Moni D., Jackuline (International Journal of Intelligent Systems and Applications in Engineering, 2024)
In India ranks first for the highest diabetic population, surpassing 100 million individuals, and is known as the "Diabetic Capital of the World." Almost 15–25% of diabetic patients are suffering from diabetic foot ulcers, considered non- healing acute and chronic wounds that lead to amputation. The treatment is also prolonged and highly expensive, which is not affordable for poor people. The new Vacuum-Assisted Closure (VAC) device is an advanced method of conventional closure designed to treat multiple patients. It can also be extended to four patients, where a minimum of 2–4 patients can be treated. The primary advancement is the isolation of internal and external circuits. This setup provides infection-free treatment for patients. This single device can provide parameters for treating different types of wounds with different therapeutic requirements. This device comprises eight heavy-duty pumps that help in treating in different modes and can still be used as a portable device. Since it is provided with multiple inlet and outlet ports, it can be used in public hospitals where it is difficult to provide treatment for more than 100 patients per day with diabetic foot ulcers. This single device can minimise the number of VAC devices used and maximise the number of patients treated. Almost 200 patients with diabetic foot ulcers were engaged in and treated with this VAC therapy. The study demonstrates that the Multi-Patient VAC Therapy System helps in faster granulation tissue closure and a better graft rate. A technical assessment has also been performed for each prototype model.